2018
DOI: 10.1038/s41598-018-28345-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of growth and production parameters of walnut (Juglans regia) saplings with response surface methodology

Abstract: Straw mulching is an effective conservation tillage tool that utilizes waste resources and reduces environmental pollution. To determine the optimal levels of quality, placement and quantity of straw mulching, we performed a field experiment that used the Box–Behnken design combined with response surface methodology. The treatments designed for walnut saplings (Juglans regia) considered three independent variables: quality, placement, and quantity of straw mulching. Tree height of walnut saplings (THW) and net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, the mix straw mulching treatments with high SI and low EI values at different straw mulching distances were in quadrant C, which indicates a structured food web, medium soil enrichment, a moderately high C/N ratio, fungal decomposition channels, and no disturbance. Our previous research suggested that the mix straw mulching treatment had a moderate carbon nitrogen ratio (C:N) and that mix straw degrades more quickly than rice straw or rapeseed straw 9 . In addition, the mix straw may have provided stable moisture content and higher dissolved organic carbon and dissolved organic nitrogen than rice straw or rapeseed straw (Table 1 ), thus increasing nutrient availability and soil fertility levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mix straw mulching treatments with high SI and low EI values at different straw mulching distances were in quadrant C, which indicates a structured food web, medium soil enrichment, a moderately high C/N ratio, fungal decomposition channels, and no disturbance. Our previous research suggested that the mix straw mulching treatment had a moderate carbon nitrogen ratio (C:N) and that mix straw degrades more quickly than rice straw or rapeseed straw 9 . In addition, the mix straw may have provided stable moisture content and higher dissolved organic carbon and dissolved organic nitrogen than rice straw or rapeseed straw (Table 1 ), thus increasing nutrient availability and soil fertility levels.…”
Section: Discussionmentioning
confidence: 99%
“…With the growth of young walnut trees, the canopy width increases each year, so it is reasonable to designate the canopy radius at the coverage distance, considering the effect of canopy shading. In addition, we have previously reported that suitable straw mulching materials can promote the growth of walnut trees and increase the potential yield 9 . Therefore, it is an important step for the sustainable management of walnut orchards to determine suitable materials for straw mulch and location for straw mulch placement.…”
Section: Introductionmentioning
confidence: 99%
“…The walnut ( Juglans regia L.) is an economically important fruit tree worldwide with various health benefits (Song et al., 2018; Su et al., 2020). The walnut flower, one of the main by‐products from the production of walnuts, has high nutritive value and has always been used as traditional food and Chinese Medicine in China (Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by the reported standard deviation (1.09), the values are close to average, that is, their dispersion is low. According to this study, the derived model's adequacy precision is 55.19, indicating it is suitable for application within the design space (Song et al, 2018). This preprint research paper has not been peer reviewed.…”
Section: Design Of Experimentsmentioning
confidence: 79%